Economic Value Added: A Yardstick for Performance Measurement - Sengupta, Suchismita; Dutta, Avijan (Indian Journal of Finance, 2011)
Economic Value Added (EVA) is one the hottest topics in the area of performance measurement today. More and more companies are adopting the EVA model to reinforce its commitment to the creation of shareholder value. The EVA analysis starts with the premise that investors are primarily concerned with the excess return above the cost of capital. This return can be directly compared with the return expected by the investors, the company’s WACC. The value is created / destroyed if the business generates a return above/ below its cost of capital. This paper examines the concept of EVA and explains how these methods are different from other traditional methods of performance measurement. The paper lists out various benefits of EVA with suitable examples from some of the Indian companies, who have implemented EVA. The paper also points out the various limitations of EVA as a tool of performance measurement.